Hydrophilic silver nanoparticles with tunable optical properties: application for the detection of heavy metals in water - Prosposito, Paolo; Mochi, Federico; Ciotta, Erica; Casalboni, Mauro; De Matteis, Fabio; Venditti, Iole; Fontana, Laura; Testa, Giovanna; Fratoddi, Ilaria (Beilstein Journal of Nanotechnology, 2016)
Due their excellent chemo-physical properties and ability to exhibit surface plasmon resonance, silver nanoparticles (AgNPs) have become a material of choice in various applications, such as nanosensors, electronic devices, nanobiotechnology and nanomedicine. In particular, from the environmental monitoring perspective, sensors based on silver nanoparticles are in great demand because of their antibacterial and inexpensive synthetic method. In the present study, we synthesized AgNPs in water phase using silver nitrate as precursor molecules, hydrophilic thiol (3-mercapto-1-propanesulfonic acid sodium salt, 3MPS) and sodium borohydride as capping and reducing agents, respectively. The AgNPs were characterized using techniques such as surface plasmon resonance (SPR) spectroscopy, dynamic light scattering (DLS), zeta potential (ζ-potential) measurements and scanning tunneling microscopy (STM). Further, to demonstrate the environmental application of our AgNPs, we also applied them for heavy metal sensing by detecting visible color modification due to SPR spectral changes. We found that these negatively charged AgNPs show good response to nickel (II) and presented good sensibility properties for the detection of low amount of ions in water in the working range of 1.0–0.1 ppm.
Keywords: heavy metal sensor; nickel (II); optical materials; optical sensors; silver nanoparticles